ANALISIS KESALAHAN BERBAHASA ARAB PADA SKRIPSI MAHASISWA JURUSAN BAHASA DAN SASTRA ARAB - Haniah, Haniah (Arabi : Journal of Arabic Studies, 2018)
This study aims to describe and explore: 1) Forms of hamzah writing errors, phonological errors, morphology, syntax and semantics in the students' thesis that are further evaluated and improved. 2) Factors causing language errors in students' thesis. 3) Solution to solve the problem of language error in writing thesis. This study used a qualitative content analysis approach to language errors on 3 thesis samples of academic year 2015/2016. The results showed that there was a mistake in writing the hamzah at the beginning of the word on the hamzah qath'i and hamzah washl, as well as in the middle of the word is the misplacement of alif or waw or nibrah letters under the hamzah. The solution offered was the need for Arabic learning innovation by faculty, students refer back to mu'jam in choosing the right words, improving writing skills with continuous practice, and seriousness in writing thesis.